2018
DOI: 10.1186/s12862-018-1147-8
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the evolution of the heterotrimeric G protein α subunit in Metazoa

Abstract: BackgroundHeterotrimeric G proteins are fundamental signaling proteins composed of three subunits, Gα and a Gβγ dimer. The role of Gα as a molecular switch is critical for transmitting and amplifying intracellular signaling cascades initiated by an activated G protein Coupled Receptor (GPCR). Despite their biochemical and therapeutic importance, the study of G protein evolution has been limited to the scope of a few model organisms. Furthermore, of the five primary Gα subfamilies, the underlying gene structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 130 publications
2
18
0
Order By: Relevance
“…Previous X-ray crystallographic analysis revealed that G proteins from different organisms and subclasses share nearly identical structural features (916). They are composed of two domains, a GTPase “Ras-like” domain that is conserved in all members of the GTPase superfamily and is homologous to the monomeric GTPase Ras and an all-α-helical domain that is unique to heterotrimeric G proteins (17, 18).…”
Section: Introductionmentioning
confidence: 99%
“…Previous X-ray crystallographic analysis revealed that G proteins from different organisms and subclasses share nearly identical structural features (916). They are composed of two domains, a GTPase “Ras-like” domain that is conserved in all members of the GTPase superfamily and is homologous to the monomeric GTPase Ras and an all-α-helical domain that is unique to heterotrimeric G proteins (17, 18).…”
Section: Introductionmentioning
confidence: 99%
“…G protein-coupled receptors (GPCRs) are responsible for the transduction of an extracellular stimuli into the cell. Inside the cell the stimulus is recognized by the heterotrimeric αβγ G proteins as downstream effectors to regulate a wide variety of physiological processes. , There are four major families of G proteins (G s , G i/o , G q/11 , G 12/13 ) which share their molecular architecture and basic signaling mechanism. The α subunit of the heterotrimeric G protein consists of two domains: the GTP-binding (Ras) domain and the α-helical domain , which are connected by two hinge regions, called “linker I” and “switch I” tightly enclosing the guanine nucleotide. , In order to release and exchange the nucleotide, domain separation must occur either spontaneously or in response to a structural change, which was induced by the activated GPCR acting as a nucleotide exchange factor. Additionally, the α, β, and γ subunits of the G protein dissociate and trigger the cellular responses through their downstream signaling cascades . Like GPCRs, which represent a major drug target class comprising the largest family of membrane protein receptors, the downstream G proteins represent promising drug targets .…”
Section: Introductionmentioning
confidence: 99%
“…GC, PDE, and PLC are key signal transducers of ciliary and rhabdomeric opsin pathways, initiated through the binding of Goα, Gtα, and Gqα ( Lamb, 2013 ; Leung and Montell, 2017 ; Oakley and Pankey, 2008 ; Plachetzki and Oakley, 2007 ). Although Amphimedon possess a Gtα gene and two Gqα genes ( Krishnan and Schiöth, 2015 ; Lokits et al., 2018 ), they are not differentially expressed in the pigment ring over other cell types, providing no support for the use of one pathway over another. However, the larval behavioral assays suggest that the immediate downstream targets of the PLC pathway are conserved.…”
Section: Discussionmentioning
confidence: 99%